Delta-subunit-containing GABAA-receptors mediate tonic inhibition in paracapsular cells of the mouse amygdala - Marowsky, Anne; Vogt, Kaspar E. (Frontiers in Neural Circuits, 2014)
The intercalated paracapsular cells (pcs) are small GABAergic interneurons that form densely populated clusters surrounding the basolateral (BLA) complex of the amygdala. Their main task in the amygdala circuitry appears to be the control of information flow, as they act as an inhibitory interface between input and output nuclei. Modulation of their activity is thus thought to affect amygdala output and the generation of fear and anxiety. Recent evidence indicates that pcs express benzodiazepine (BZ)-sensitive GABAA receptor (GABAAR) variants containing the α2- and α3-subunit for transmission of postsynaptic currents, yet little is known about the expression of extrasynaptic GABAARs, mediating tonic inhibition and regulating neuronal excitability. Here, we show that pcs from the lateral and medial intercalated cell cluster (l- and mITC, respectively) express a tonic GABAergic conductance that could be significantly increased in a concentration-dependent manner by the δ-preferring GABAAR agonist THIP (0.5-10 µM), but not by the BZ diazepam (1 µM). The neurosteroid THDOC (300 nM) also increased tonic currents in pcs significantly, but only in the presence of additional GABA (5 µM). Immunohistochemical stainings revealed that both the δ-GABAAR and the α4-GABAAR subunit are expressed throughout all ITCs, while no staining for the α5-GABAAR subunit could be detected. Moreover, 1 µM THIP dampened excitability in pcs most likely by increasing shunting inhibition. In line with this, THIP significantly decreased lITC-generated inhibition in target cells residing in the BLA nucleus by 30%. Taken together these results demonstrate for the first time that pcs express a tonic inhibitory conductance mediated most likely by α4/δ-containing GABAARs. This data also suggest that δ-GABAAR targeting compounds might possibly interfere with pcs-related neuronal processes such as fear extinction.